THE SOCIO-DECISIONAL AXES OF POST-CONFINEMENT CLASSES RESUMPTION IN TIMES OF COVID-19 IN CAMEROON: BETWEEN EDUCATIONAL PRIORITY AND EDUCATIONAL INEQUALITY - Russel Ponty ZAMBO (Universitaria Publishing House, Craiova, 2021)
This research aims to better understand the decision-making process to support the resumption of post-confinement classes during the corona virus health crisis in Cameroon. Data collection and analysis were based on a qualitative methodology through documentary research. The results show that in Cameroon, the resumption of post-confinement classes was more based on the principles of education priority and educational inequality in the order to respond to different levels of issues, both socio-educational, socio-political and socio-health, the decisions that organize this recovery can be split into two majors axes: the central axis and the peripheral axis.